2009
DOI: 10.1016/j.jana.2009.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Peer-Group Intervention on Occupation-Related Behaviors for Urban Hospital Workers in Malawi

Abstract: Using a pre- and post-test design with no control group, we evaluated the impact of a peer group intervention on work-related knowledge and behavior for health workers at an urban hospital in Malawi. We surveyed unmatched random samples of health workers, observed workers on the job, and interviewed clients about hospital services at baseline and at 6 months after the intervention. Universal precautions (UP) knowledge, reported hand washing, and reported client teaching were significantly higher at the final e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
(68 reference statements)
1
12
0
1
Order By: Relevance
“…Findings from our pilot study were consistent with previously reported observational studies, in which the knowledge of HIV in students and health professionals from Chile and other countries has been weak in several domains (Chimango et al, 2009; Ferrer et al, 2007; Kaponda et al, 2009; Norr et al, 2006). In addition, interventions for health professions university students have also shown significant improvement in knowledge and positive attitudes after education (Pickles et al, 2009; Valois et al, 2001; Yiu et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Findings from our pilot study were consistent with previously reported observational studies, in which the knowledge of HIV in students and health professionals from Chile and other countries has been weak in several domains (Chimango et al, 2009; Ferrer et al, 2007; Kaponda et al, 2009; Norr et al, 2006). In addition, interventions for health professions university students have also shown significant improvement in knowledge and positive attitudes after education (Pickles et al, 2009; Valois et al, 2001; Yiu et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…An HIV intervention for rural health workers in Malawi was found to be effective in improving both personal and job-related HIV knowledge, attitudes, and behaviors for rural and urban health workers, including more use of standard precautions, more HIV prevention teaching, and respectful interactions with clients (Chimango et al, 2009; Kaponda et al, 2009; Norr et al, 2006). Participants’ general knowledge of universal precautions (cleaning, glove wearing, hand washing, and sharps) improved from 77.43% at baseline to 79.23% at postintervention, a small yet statistically significant development (Chimango et.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention, Mano a Mano Para Trabajadores de Salud , is a professionally-assisted peer group intervention adapted from a peer group intervention successfully used for health workers in Malawi (Chimango et al, 2009; Mbeba et al, in press). The intervention's conceptual framework and cultural tailoring to Chile based on a formative evaluation were described above.…”
Section: Methodsmentioning
confidence: 99%
“…The U.S.-based coauthors and their colleagues in Malawi have developed and tested a peer group intervention in Malawi that improved health workers' personal and work-related knowledge, attitudes, and behaviors (Chimango et al, 2009; Jere et al, 2010; Kaponda et al, 2009, Mbeba et al, 2011). The intervention's delivery was based on the WHO primary health care model of health worker-community collaboration to address health issues.…”
Section: Hiv Prevention Interventions For Health Workersmentioning
confidence: 99%